Artificial Light at Night (ALAN) as an Emerging Urban Stressor for Tree Phenology and Physiology: A Review - Luisa Friulla; Laura Varone (Urban Science)
Artificial light at night (ALAN) is an expanding environmental issue, particularly in urban areas. This review aimed to present the state of the art regarding the impact of ALAN on specific and interrelated aspects related to physiological processes and life cycle events in tree species. The reviewed studies highlighted the multifaceted effects of artificial light on plants, offering insights and perspectives to guide future research in this evolving and stimulating field. ALAN disrupts circadian rhythms, alters photoperiodic responses, and affects photosynthesis and carbohydrate metabolism. Changes in phenology such as delayed senescence and altered budburst timing demonstrated species-specific responses, often compounded by other urban stressors like heat and drought. Despite an increased interest, knowledge gaps remain concerning the species-specific responses and the effects of light spectra as well as the long-term consequences on tree physiology. These gaps highlight the need for integrated research approaches and urban planning strategies to mitigate ALAN effects, ensuring the resilience of urban trees and preserving ecosystem services in the context of growing urbanization and climate change.